THE USE OF FIGURATIVE LANGUAGE AND IMAGERY IN SONGS’ LYRICS - Gunawan Tambunsaribu; Bob Morison Sigalingging (Prodi Sastra Inggris UKI, 2024)
In literary works, most authors express their feelings by using figurative language in their writing. The languages used in literary works usually represent the explicit and implicit feelings and thoughts of their characters. Someone may use figurative language to create unique and aesthetic communication. This study aims to find out the use of figurative language and imagery found in the two songs from Bruno Mars’ album entitled